Utilization of Coffee Waste as Active Charcoal For Purification of Waste Cooking Oil - Salma Husna Sukmawati; Sunarto Sunarto (Universitas Negeri Yogyakarta, 2021)
This research aims to find the comparison of the chemical-physical characters of coffee waste activated charcoal using ZnCl2 with HCl, to calculate the highest adsorption efficiency, and to determine the quality of waste cooking oil after purification. The washed and dried of coffee waste are carbonized by the temperature 700oC and chemically activated using ZnCl2 5% and HCl 5%. The adsorption process used by batch system. The object of this research is the character of activated charcoal from coffee waste such as water content, ash content, iodine adsorption capacity of activated charcoal, peroxide number and free fatty acid (FFA) number of waste cooking oil before and after purification. Morphological analysis of activated charcoal was carried out using Scanning Electron Microscope (SEM). Analysis of the number of peroxide and FFA were carried out respectively using the titration method. The results of the characterization of activated charcoal showed that the activated charcoal with ZnCl2 5% activator had a water content of 6.55%, an ash content of 6.046%, adsorption of iodine 1039.5 mg/g, and had clean and wide pores. Activated charcoal with HCl 5% activator has a water content of 7.25%, an ash content of 7.55%, and 1008 mg/g of iodine adsorption. The highest adsorption efficiency of activated charcoal was 49.9749% in reducing the peroxide number and 50.1113% for reducing FFA, these results were obtained at 3 hours contact time with 3 g adsorbent mass. The peroxide number in the waste cooking oil that has been purified has not qualitified the standard SNI 01-3741-2013, but the FFA at 3 hours contact time with 3 g adsorbent mass qualitified the standard